2016
DOI: 10.1155/2016/9421203
|View full text |Cite
|
Sign up to set email alerts
|

PEDOT:PSS-Containing Nanohydroxyapatite/Chitosan Conductive Bionanocomposite Scaffold: Fabrication and Evaluation

Abstract: Conductive poly(3,4-ethylenedioxythiophene)-poly(4-styrene sulfonate) (PEDOT:PSS) was incorporated into nanohydroxyapatite/chitosan (nHA/CS) composite scaffolds through a freezing and lyophilization technique. The bionanocomposite conductive scaffold was then characterized using several techniques. A scanning electron microscope image showed that the nHA and PEDOT:PSS were dispersed homogeneously in the chitosan matrix, which was also confirmed by energy-dispersive X-ray (EDX) analysis. The conductive properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…It is well-known that mechanical properties and cytocompatibility and are very important for the successful proliferation, growth, and differentiation of cell cultures. Thus, many studies on CP-based scaffolds focused on the incorporation of biopolymers such as collagen, 41,52 gelatin, 625,626 alginate, 626,627 chitosan, 628 silk fibroin, 629 and cellular-based gels, such as cardiogel. 455 Indeed, recent studies by our group demonstrated the use of PEDOT:PSS scaffolds containing collagen for enhancing the mechanical properties and promoting differentiation of neural crest stem (NCS) cells.…”
Section: D Cell Culturesmentioning
confidence: 99%
“…It is well-known that mechanical properties and cytocompatibility and are very important for the successful proliferation, growth, and differentiation of cell cultures. Thus, many studies on CP-based scaffolds focused on the incorporation of biopolymers such as collagen, 41,52 gelatin, 625,626 alginate, 626,627 chitosan, 628 silk fibroin, 629 and cellular-based gels, such as cardiogel. 455 Indeed, recent studies by our group demonstrated the use of PEDOT:PSS scaffolds containing collagen for enhancing the mechanical properties and promoting differentiation of neural crest stem (NCS) cells.…”
Section: D Cell Culturesmentioning
confidence: 99%
“…They also found that both the compressive modulus and the yield strength of the chitosan increased to 0.5–1.0 MPa and 5–5.5 MPa, respectively, with the addition of nHAp and PEDOT: PSS. Unfortunately, the CS/nHAp/PEDOT: PSS had poor biodegradability, due to the strong bonding between PEDOT: PSS and the rest of the substrate chains [ 26 ]. Meanwhile, Iandolo et al (2020) prepared highly porous biomimetic scaffolds by combining the PEDOT: PSS with collagen type I (the most abundant protein in bone) for inactive support.…”
Section: Physical Properties Of Conductive-polymeric Scaffoldsmentioning
confidence: 99%
“…Another study demonstrated that the addition of conductive PEDOT: PSS in nHAp/chitosan composite scaffolds using the lyophilisation method reduced the scaffold’s biodegradability rate in the PBS solution. Although the scaffold with PEDOT: PSS had low biodegradability, its mechanical properties were consistent [ 26 ]. Lari et al (2020) attempted to decrease the wettability, while dialling up the mechanical properties, of PEDOT: PSS/nHA/CS biocomposite, by integrating polycaprolactone (PCL) into the scaffold.…”
Section: Common Conductive and Biodegradable Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a particular type of scaffold, conducting polymer scaffolds are currently interesting for their additional advantage of promoting cell growth by electrical stimulation. Conducting polymers used in tissue engineering are polypyrrole, , polyaniline, , polythiophenes, , and poly­(3,4-ethylenedioxythiophene) (PEDOT). They have been used to enhance bone, muscle, and nerve tissue regeneration . Moreover, they are also used in drug delivery, with drugs bound in the scaffolds and released through an electrical signal .…”
Section: Introductionmentioning
confidence: 99%